Evaluation of Comorbidities in Patients with OSAS and Simple Snoring - Ömer Hızlı; Müge Özcan; Adnan Ünal (The Scientific World Journal)
Aim. OSAS is a disease characterized by repetitive air flow constraint or cessation due to airway collapse. Diseases that frequently coexist with OSAS and simple snoring were evaluated in this study. Materials and Methods. This study was conducted in the Otorhinolaryngology Department of the Ankara Numune Hospital between April 2008 and April 2010 with 130 patients who presented with the complaints of snoring, witnessed apnea, and daytime drowsiness. Presence of chronic disease was compared to the demographics, BMIs, Epworth Scale scores, polysomnography, and physical examination findings. Results. Comorbid diseases were present in 56 (43.1%) of the patients, and the most presented disease group was cardiovascular system diseases. Age, BMI, daytime drowsiness, and frequency of septum deviation were observed at higher rates in patients with chronic disease. Age, BMI, and frequency of septum deviation were associated with cardiovascular diseases. Endocrine disease was found to increase with decreased oxygen saturation. Neuropsychiatric diseases were associated with daytime drowsiness and age. The mean age was lower in cases with cigarette smoking compared to cases without. Conclusion. Frequency of the comorbidities mostly increased with age as expected. Comorbid diseases were also associated with obesity and daytime drowsiness. Cigarette smoking was associated with early-age disease.